ANALYSIS OF MERGER OF SBI & ITS ASSOCIATES - Khurana, Bharat (International Journal of Research -GRANTHAALAYAH, 2017)
Merger of SBI with its 5 associate banks and Bharatiya Mahila Bank which took place on 1 April, 2017 is the largest merger in history of Indian Banking Industry. The research has been conducted to know from where the journey of SBI to reach this point of success where post-merger it is at 45th position among top banks of the world. The focus of this paper has been placed on reasons of this merger and also, after effects of merger has also been discussed.